Congenital Asplenia in a Surgical Patient (Journal of Science and Technology, 2016)
Congenital asplenia is rare and could occur sporadically or less commonly as part of a syndrome. Sporadic or isolated congenital asphenia is not usually associated with significant morbidity. Congenical isolated asphenia can be present as septicaemia, commonly pneumococcal, hence the importance of screening the peripheral blood for Howell-Jolly bodies. Abdominal imaging becomes necessary if screening is positive. An isolated case of congenital asphenia is discovered by chance in a 69 year-old man, after falling off a ladder from a height of about 15 feet. Standard surgical procedure was followedin managing the patient. Here, abdominal ultrasound commented on the absence of the spleen followed trauma. Fracture of the spleen was suspected hence exploratory laparotomy was performed. To the best of our knowledge, this report is probably an isolated abnormality and most likely a sporadic case.